Impact of Na/Al Ratio on the Extent of Alkali-Activation Reaction: Non-linearity and Diminishing Returns - Abdelrahman, Omar; Garg, Nishant (Frontiers in Chemistry, 2022)
To address the high CO2 footprint associated with cement production, many alternative, sustainable binders are now gaining worldwide attention – including alkali-activated materials (AAMs). The alkali-activation reaction of metakaolin is a fairly complex process involving transformation of one amorphous reactant (precursor metakaolin) into another amorphous product or products (N-A-S-H gel and/or disordered zeolite type phases). In spite of this complexity, researchers in the past two decades have gained significant knowledge on the nature of this reaction at multiple scales. Understanding and developing a clear relationship between the alkalinity of the mix and the extent of reaction is of high interest for practical applications. However, detailed and thorough investigations on this important relationship are limited. Here, in this study, we address this gap by systematically investigating a series of AAM samples with a wide range of Na/Al ratios (0.5 – 1.8) using 7 different yet complementary analytical techniques (isothermal calorimetry, FTIR, XRD, TGA, NMR, and Raman imaging). Applied in tandem, these tools reveal a clear but non-linear relationship between the Na/Al ratio and the extent of alkali-activation reaction indicating diminishing returns at higher Na/Al ratios, where higher Na/Al ratios cause an increase in the degree of reaction until a certain point at which the increase in Na/Al ratio does not significantly affect the reaction kinetics, but may affect the gel polymerization. These findings could potentially aid decision making for commercial applications of AAMs where alkalinity of the mix is an important parameter for performance as well as safety.